The Future of Work in the Age of Automation: Proceedings of a Workshop on Norbert Wieners 21st Century Legacy - Love, Heather A.; Adamson, Greg; James, Mallory; Lajoie, Jason; Mareels, Iven; Pearl, Zach; Schiff, Daniel S.; Schmitt, Ketra; Arohi, Thirumala; Buchanan, John; Camarena, Stephanie; Kaevats, Marten; et al. (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2025)
This article synthesizes the insights gained through presentations and discussions at the 2023 IEEE Workshop on Norbert Wiener in the 21st Century (21CW2023), which focused on The Future of Work in the Age of Automation. Hosted at Purdue University, this interdisciplinary convening of technologists, social scientists, and humanists explored the impacts of automation on labor, drawing on Wiener's legacy of insights as a backdrop to examine the technologically mediated future we face in coming decades. The workshop presented a rare opportunity to reflect critically on these issues at a pivotal moment in human and technological history, and to elicit underappreciated dimensions. Areas of focus include: the qualitative and quantitative losses associated with automation and AI, the impacts automation has for questions about the meaningfulness of work, the challenges we face related to uncertainty and lack of predictability in technological advancement, and the opportunities that exist for centering human values and agency in these conversations. While acknowledging many items for concern in the context of automation in the future of work, such as the domination of economic narratives, a potential loss of qualitative texture, and the neglect of certain issues key to human identity, the authors conclude by offering optimistic visions-or calls-for redefining value and labor, preserving human agency, and embracing creative problem-solving.
Keywords: Future of work; automation; Norbert Wiener; cybernetics; technology ethics; artificial intelligence; meaning of work; ethical innovation; limits of predictability; ARTIFICIAL-INTELLIGENCE; CRIME; LABOR; CARE; Engineering; Social Issues